2022
DOI: 10.1021/acs.molpharmaceut.2c00752
|View full text |Cite
|
Sign up to set email alerts
|

N-2-Hydroxypropylmethacrylamide–Polycaprolactone Polymeric Micelles in Co-delivery of Proteasome Inhibitor and Polyphenol: Exploration of Synergism or Antagonism

Abstract: Breast cancer leads to the highest mortality among women resulting in a major clinical burden. Multidrug therapy is more efficient in such patients compared to monodrug therapy. Simultaneous combinatorial or co-delivery garnered significant interest in the past years. Caffeic acid (CFA) (a natural polyphenol) has received growing attention because of its anticarcinogenic and antioxidant potential. Bortezomib (BTZ) is a proteasome inhibitor and may be explored for treating breast cancer. Despite its high antica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…These factors may influence sensitivity to therapy and polyphenol's ability to modulate cell response to anticancer therapy. [30,66,70] Our results from 22Rv1-xenograft studies showed somewhat less efficacious effects in terms of reducing the tumor volume. Intriguingly, while tumors under combined treatment appeared to have a higher tumor volume, histopathology of these tumors demonstrated a higher percentage of intratumoral necrosis compared with vehicle-treated groups.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…These factors may influence sensitivity to therapy and polyphenol's ability to modulate cell response to anticancer therapy. [30,66,70] Our results from 22Rv1-xenograft studies showed somewhat less efficacious effects in terms of reducing the tumor volume. Intriguingly, while tumors under combined treatment appeared to have a higher tumor volume, histopathology of these tumors demonstrated a higher percentage of intratumoral necrosis compared with vehicle-treated groups.…”
Section: Discussionmentioning
confidence: 69%
“…Notably, other studies have described the antagonism of natural polyphenols with some anticancer drugs. [ 30,70 ] Our in vitro cell viability results with various dose combinations indicated the importance of appropriate doses in co‐treatment approaches to achieve additive or synergistic effects. Moreover, it has been reported that natural products and individual polyphenols at lower doses exert more potent anti‐inflammatory and anticancer effects than at higher doses when used in vivo.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation